Assessment of patient satisfaction with pharmacy service and associated factors in public hospitals, Eastern Ethiopia. (May 2020) - Ayele, Yohanes; Hawulte, Behailu; Feto, Tilaye; Basker, G Vijai; Bacha, Yadeta Dessie
Background: A comprehensive understanding of the extent of patient satisfaction and its determinants are crucial in improving the quality of service. Hence, this research was designed to measure patient satisfaction with pharmacy service. Methods: A cross-sectional study was conducted among 422 patients to assess satisfaction with pharmacy service in public hospitals located in Eastern Ethiopia from September to January 2018. Data were collected through an exit interview using structured questionnaires. Then, it was entered into EpiData version 3.1 and exported to STATA version 14.2 for analysis. Associations between dependent and independent variables were assessed by multiple logistic regression using an adjusted odds ratio at a 95% confidence interval and the p values of less than 0.05. Results: A total of 407 samples were included in the final analysis. The mean overall satisfaction of clients measured out of five was 2.29 (standard deviation ± 0.56). The proportion of overall satisfaction was 46.19%. Patients within the age range of 26–35 years and 36–50 years were found to have 50% (adjusted odds ratio = 0.5, 95% confidence interval: 0.3, 0.9) and 60% (adjusted odds ratio = 0.4, 95% confidence interval: 0.2, 0.8) decreased likelihood of satisfaction compared with patients within the range of 18–25 years, respectively. Likewise, patients who attended only secondary education compared to their counterpart (a certificate and above) were less likely to be satisfied (adjusted odds ratio = 0.4, 95% confidence interval: 0.2, 0.8). In contrast, rural dwellers and patients who collected all their medications from the respective hospital were found to be more satisfied compared with their equivalent (adjusted odds ratio = 3, 95% confidence interval: 1.8, 5.2) and (adjusted odds ratio = 2.2, 95% confidence interval: 1.4, 3.5), respectively. Conclusion: Patient satisfaction with pharmacy service was found to be very low considering the current health-care system movement toward delivering quality service. Hence, health-care providers and administrators should give due attention to contributing factors in order to improve the quality of service and ultimately increase patient satisfaction.